2020
DOI: 10.3846/jbem.2020.12280
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Technological Turbulence, Flow Experience, Innovation Performance and Small Firm Growth

Abstract: The main objective of the paper is to address the question of how to foster innovation and small firm growth under different levels of technological turbulence. Specifically, the paper examines the relationship among risk-taking, arising from different levels of technological turbulence, flow experience, innovation and small firm growth (i.e. market share and ROI growth). The underlying premise of our research is that there are substantial differences in low and high technological environments in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
1
0
4
Order By: Relevance
“…La turbulencia tecnológica hace referencia al cambio tecnológico que sucede a lo largo del tiempo dentro de una industria, producción o en los mismos productos, y al que las compañías deben saber adaptarse para sobrevivir (Martin et al, 2020). Un ambiente de turbulencia tecnológica implica que se tomen nuevos riesgos y afronten decisiones estratégicas, lo cual sucede dentro de un entorno de alta incertidumbre (Slavec Gomezel & Aleksić, 2020). La turbulencia tecnológica suele crear alteraciones que fuerzan a las compañías a apropiarse de nuevas tendencias y puede verse como una amenaza cuando aquellas tendencias se presentan como disruptivas (Martin et al, 2020).…”
Section: Turbulencia Tecnológicaunclassified
See 2 more Smart Citations
“…La turbulencia tecnológica hace referencia al cambio tecnológico que sucede a lo largo del tiempo dentro de una industria, producción o en los mismos productos, y al que las compañías deben saber adaptarse para sobrevivir (Martin et al, 2020). Un ambiente de turbulencia tecnológica implica que se tomen nuevos riesgos y afronten decisiones estratégicas, lo cual sucede dentro de un entorno de alta incertidumbre (Slavec Gomezel & Aleksić, 2020). La turbulencia tecnológica suele crear alteraciones que fuerzan a las compañías a apropiarse de nuevas tendencias y puede verse como una amenaza cuando aquellas tendencias se presentan como disruptivas (Martin et al, 2020).…”
Section: Turbulencia Tecnológicaunclassified
“…Esto es cierto en particular para los sectores tecnológicos (Neştian et al, 2020). La turbulencia tecnológica implica tomar decisiones estratégicas y nuevos riesgos (Slavec Gomezel & Aleksić, 2020), dado que con frecuencia involucra cambios disruptivos para las industrias (Martin et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Bu çalışmaların sonuçlarına göre ise firmaların içerisinde bulunduğu teknolojik türbülansın seviyesi arttıkça firmanın sahip olduğu bilgilerin geçerliliği ve güvenilirliği azaldığı için mevcut bilgi seviyesi azalmaktadır (Zhao, 2020). Bu durum firmaları yeni bilgiye daha hızlı şekilde ulaşmaya (Song & Montoya-Weiss, 2001), daha fazla risk almaya (Pratono,2018), teknolojiyi kullanma niyetinin artmasına (Pinheiro, 2020) ve seçenekler arasındaki en iyi teknolojiyi seçmeye (Gomezel & Aleksic, 2020) zorlar. Bu durum ise firmaları daha çok inovatif olmaya yönlendirir (Zhao, 2020).…”
Section: Kavramsal çErçeveunclassified
“…The turbulent environment drives companies to innovate, and this innovation is not only for the development of new products but also on business processes, forms of organizational learning between supply chains, and knowledge exchanges [9]. Gomezel found that technological turbulence can seriously affect product development [28]. Through an empirical study of 553 Japanese development projects, Song et al found that technological turbulence has a significant impact on the ability to sustain innovation, such as new product development [29].…”
Section: Environmental Turbulencementioning
confidence: 99%